Einai bebaiōs Iudaios (Ant XX,38): "authentisches Jude-Sein" bei Josephus und Paulus - Tiwald, Markus (Protokolle zur Bibel, 2008)
For a long time biblical scholars have stressed the gap between the theology of Paul and rabbinic thought. But recent research in second temple Judaism has shown that rabbinic Judaism only emerged in the second century C.E. So the enumeration of differences between Paul and rabbinic teachings are no longer a valid proof to demonstrate that Paul in his time as follower of Jesus had rejected his Jewishness or „abrogated“ the Torah. In Early Judaism a wide range of Jewish positions were possible. So Paul even in his Christian time continues to be a Jew. A view on Josephus and other authors of Early Judaism may serve as a proof for this interpretation.